Dažādi klusās dabas risinājumi Talsu Mākslas skolas 2.kursā iedvesmojoties no Pīta Mondriana daiļrades - Sapiega, Ildze (Latvijas Universitāte, 2015)
Diplomdarba tēma ir „Dažādi klusās dabas risinājumi Talsu Mākslas skolas 2.kursā, iedvesmojoties no Pīta Mondriana daiļrades”. Šī darba mērķis ir, balstoties uz teorijas izpēti par Pīta Mondriana daiļradi un jauniešu vecumposma īpašībām, rast risinājumus, kā mērķtiecīgi ievadīt audzēkņus izprast un spēt patstāvīgi risināt klusās dabas uzstādījumus, iedvesmojoties no Pīta Mondriana gleznu reprodukcijām. Lai šo mērķi sasniegtu, tiek apskatīta Pīta Mondriana biogrāfija un daiļrades dažādie posmi, pētīts, kā attīstās stilistika, glezniecības paņēmieni. Tāpat diplomdarbā tiek pētītas audzēkņu vecumposma īpašības, tālāk izglītošana, audzināšanas aspekti, lai veiksmīgi varētu tam pielāgot uzdevumu kopu un aprobēt to, vienlaicīgi balstoties uz Talsu mākslas skolas izstrādātajiem profesionālās ievirzes programmas pamatiem. Atslēgvārdi: Pīts Mondrians, postimpresionisms, abstrakcionisms, neoplasticisms, gleznu sērijas, triepiens, klusā daba.

The theme of Diploma Paper is „Different solutions of still life in Talsu Art School 2nd course, inspired by Piet Mondrian’s creative work”. The aim of this work is, based on theory research of Piet Mondrian creative work and youth age group characteristics, to conduct students to understand and be able to independently solve settings of still life, inspired by Piet Mondrian painting reproductions. To achieve the goal, Piet Mondrian biography and artistic various phases is viewed, also studied the evolution of stylistics and painting techniques. Also in this Diploma paper is explored students age group characteristics, further education and education aspects to successfully adapt and approbate it, simultaneously on the basis of Talsi Art School developed professional orientation program basis. The structure of Diploma Paper consists of three chapters. The first chapter examines the Piet Mondrian biography and artistic stages, artistic development, connection with other artists of that time and artistic styles, the effect of each place where the artist lives staying. Second chapter includes basic characteristics of pedagogical activity, age group overall characteristics and characteristics in the visual arts context. It also includes approbation of the methods and evaluation criteria. In the third chapter is approve created tasks. Keywords: Piet Mondrian, post-impressionism, abstractionism, neoplasticism , brushwork, still life.
Different Solutions of Still Life in Talsu Art School 2nd Course, Inspired by Piet Mondrian’s Creative Work
Keywords: Pedagoģija